Analisis Tata Kelola Waktu Berbasis Time Management Matrix dalam Mereduksi Konflik Peran Ganda Mahasiswa-Santri - Muhamad Ngabdur Rozaq; Ahmad Majidun (NUZUM: Jurnal Manajemen & Administrasi Pendidikan, 2026)
This study aims to analyze the learning time management of Islamic Education Management undergraduate students (mahasiswa-santri) at API Syubbanul Wathon Tempuran Islamic Boarding School, Magelang, in balancing their double burden between university academic demands and boarding school commitments. A qualitative case study approach was employed, with data collection techniques utilizing in-depth interviews with six mahasiswa-santri informants and two structural administrators, complemented by participant observation and documentation. The empirical findings were examined through the lens of Stephen R. Covey's Time Management Matrix. The results indicate that mahasiswa-santri act tactically and responsively in Quadrant I (Important & Urgent) to accomplish university assignments and daily Quranic memorization. Long-term success is determined by the optimization of Quadrant II (Important & Not Urgent) through preventive habits such as progressive task completion. Although frequently encountering sociological interruptions in Quadrant III (Urgent & Not Important) due to peer conformity pressures, and digital procrastination risks in Quadrant IV (Not Urgent & Not Important), their time management efficiency remains well-maintained. In conclusion, the mahasiswa-santri time management capacity is a dialectical result of integrating internal factors, including personal agency awareness and andragogic maturity, with external factors, which encompass institutional curriculum synchronization policies, rigid communal scheduling as a social conditioning instrument, and strict supervision from boarding school administrators.